The Relationship between Households Average Formal Education Levels and Sanitation Practices in Mojo, Surabaya, Indonesia - Wardhani, Widhowati Kesoema; Harmin Sulistiyaning Titah; Mas Agus Mardyanto; Eddy Setiadi Soedjono (Industrial and Domestic Waste Management, 2025)
This study explored the relationship between households’ average formal education levels and sanitation practices. Although formal education was intended to prepare individuals for personal and professional life situations, local habits and cultural practices could sometimes be more influential than educational background, as evidenced by urinary habits practiced in the country. These habits played a crucial role in determining whether urine was disposed of in the toilet, processed in a septic tank, or directly entered the drainage system when spilled on the bathroom floor. In this study, the definition of sanitation differed from that previously outlined by the Sustainable Development Goals (SDGs). The SDGs defined sanitation based on the percentage of households that used safely managed services, including handwashing facilities. This study, however, focused on excreta disposal, desludging intervals, septic tank types, and urinary habits, such as whether urine was disposed of on the bathroom floor or in the toilet. These factors were chosen for their ability to accurately reflect the actual conditions observed in the study area. A survey was conducted among 100 households, and data were analyzed using Analysis of Variance (ANOVA). The results revealed no relationship between households’ average formal education levels and sanitation practices. This analysis suggested that other factors, such as cultural beliefs and environmental habits, may have influenced sanitation practices.